THE EFFECT OF RETURN ON ASSET, DEBT TO EQUITY RATIO AND CURRENT RATIO ON PRICE TO BOOK VALUE (CASE STUDY ON FOOD AND BEVERAGE SUBSECTOR COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE PERIOD 2019-2021) - Dinatonia Jovery Matruty; Lilian Sonya Loppies; Medellin Jesica Lawalata (SEAN Institute, 2023)
This research aims to determine the effect of return on assets, debt to equity ratio and current ratio toPrice to Book Valuein Food and Beverage companies listed on the Indonesia Stock Exchange (BEI) in 2019-2021. Companies listed on the Indonesia Stock Exchange (BEI) in the food and beverage subsector from 2019 to 2021 constitute the population of this research. Purposive sampling was used for this research, resulting in a research sample of 30 companies. This research uses secondary data obtained from the official website of the Indonesian Stock Exchange (www.idx.co.id). The E-Views 9 tool was used to perform panel data regression analysis on the data collected in this research. According to research results, ROA has a positive and significant effect on Price to Book Value. DER has a positive and significant effect on PBV and CR has a negative and insignificant effect on PBV.